Psychological Skills of Soccer Players Based On Gender Perspective (Department of Physical Education, Sport, Health and Recreation, 2019)
Abstract The studies on the psychological skills of players based on gender perspective are limited, particularly in elite soccer players. We evaluated the psychological skills of Indonesian male and female soccer players who competed in Asian Games 2018. The research method was a retrospective causal-comparative design using The Psychological Skills Inventory for Sports (PSIS-R-5) instrument. The data were analyzed using the independent sample t-test (P < 0,05) and cross tabulation techniques. The results showed that there were no significant differences in the characteristics of psychological skills between the Indonesian male and female national soccer team players. This study reveals a lack of psychological skills in soccer players, particularly in concentration and the importance of team. Therefore this research can provide scientific information for the coaches to improve the psychological skills of both male and female soccer players is needed. Future research is needed to develop and to improve the psychological skills of the professional male and female soccer players.